PENGARUH PROMOSI KESEHATAN TENTANG INISIASI MENYUSU DINI TERHADAP PENGETAHUAN IBU HAMIL PRIMIGRAVIDADI WILAYAH KERJA PUSKESMAS CIRACAS TAHUN 2020 - Annisya Lathifah (2021)
Early Initiation of Breastfeeding is the process of immediate breastfeeding for 30 minutes to 1 hour which contains immunity in the baby and reduces the risk of postpartum bleeding in the mother. Dissemination of information through health promotion increases knowledge of primigravid pregnant women (first pregnancy). This study aims to determine the effect of health promotion of early breastfeeding initiation on primigravid pregnant women's knowledge in work area of Puskesmas Ciracas. This research is qualitative research with a quasi-experimental design with a pretest-posttest control group design. The sample used was 40 respondents through accidental sampling technique by collecting data through online questionnaires and using health promotion media in the form of leaflets and video which was carried out from December 2020 to January 2021. The result showed that the implementation of health promotion using leaflet and video effect increasing knowledge of primigravid pregnant women (p= 0,000). Meanwhile, the use of leaflet and video did not have a significant difference (p= 0,096). It was concluded that there were differences in knowledge before and after health promotion using leaflets or videos. It is hoped that puskesmas can improve health promotion during the Covid-19 pandemic, especially primigravid pregnant women with other media